2021
DOI: 10.1111/irel.12288
|View full text |Cite
|
Sign up to set email alerts
|

Worker Participation in Decision‐making, Worker Sorting, and Firm Performance

Abstract: Worker participation in decision‐making is often associated with high‐wage and high‐productivity firm strategies. Using linked employer–employee data for Germany and worker fixed effects from a two‐way fixed‐effects model of wages capturing observed and unobserved worker quality, we find that plants with formal worker participation via works councils indeed employ higher quality workers. We show that worker quality is already higher in plants before council introduction and further increases after the introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…−3.7% in the service sector). These latter results are similar to previous articles using time variations as a source of identification (Grund & Schmitt, 2013; Guertzgen, 2009; Kraft & Lang, 2008; Mueller & Neuschaeffer, 2021). It is worth adding that, in both the manufacturing and the service sectors, the point estimates of the works council and works councilor premiums are not far from each other.…”
Section: Estimationssupporting
confidence: 91%
See 2 more Smart Citations
“…−3.7% in the service sector). These latter results are similar to previous articles using time variations as a source of identification (Grund & Schmitt, 2013; Guertzgen, 2009; Kraft & Lang, 2008; Mueller & Neuschaeffer, 2021). It is worth adding that, in both the manufacturing and the service sectors, the point estimates of the works council and works councilor premiums are not far from each other.…”
Section: Estimationssupporting
confidence: 91%
“…The OLS model in Table A3.3 in Appendix shows that workers in establishments with a works council earn 12% more than the rest once taken into account the standard covariates. This is very close to estimates previously measured by the literature (e.g., Addison et al 2010; Kraft & Lang, 2008; Mueller & Neuschaeffer, 2021). However, many factors may bias these estimates.…”
Section: Estimationssupporting
confidence: 91%
See 1 more Smart Citation
“…For shop-floor representation, the reform-based, quasi-experimental studies of Finnish shop-floor representation by Keskinen (2017) and find no effects on firm performance. Older studies of German shop-floor representation find mixed results (Addison, Schnabel, and Wagner, 2004;Addison, 2009), while newer studies find generally positive associations between works councils and productivity and profitability (Mueller, 2012;Mueller and Stegmaier, 2017;Jirjahn and Smith, 2018;Mueller and Neuschaeffer, 2020;Schnabel, 2020). Moreover, specifically rejecting the "hold-up" mechanism, German firms with works councils do not have lower capital investment (Addison, Schank, Schnabel, and Wagner, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For shop-floor representation, the reform-based, quasi-experimental studies of Finnish shop-floor representation by Keskinen (2017) and Harju et al (2021) found no effects on firm performance. Older studies of German shop-floor representation reported mixed results (Addison, Schnabel, and Wagner 2004; Addison 2009), while newer studies found generally positive associations between works councils and productivity and profitability (Mueller 2012; Mueller and Stegmaier 2017; Jirjahn and Smith 2018; Mueller and Neuschaeffer 2020; Schnabel 2020). Moreover, specifically rejecting the “hold-up” mechanism, German firms with works councils do not have lower capital investment (Addison, Schank, Schnabel, and Wagner 2007).…”
Section: Firm Performancementioning
confidence: 99%